2011
DOI: 10.1055/s-0031-1275244
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Chemoradiotherapy as a Standard Treatment for Squamous Cell Carcinoma of the Temporal Bone

Abstract: We sought to characterize the effectiveness of concomitant chemoradiotherapy (CCRT) for patients with squamous cell carcinoma of the temporal bone. We performed a retrospective chart review of 14 patients with cancer of the temporal bone who were provided initial treatment in our hospital from December 2001 to November 2008. Four patients with stage I tumors were treated by radiation therapy alone or with oral administration of S1. One patient with a stage II tumor was treated by radiation therapy concomitant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 16 publications
1
47
0
2
Order By: Relevance
“…On the basis of favorable oncologic results for T4 diseases obtained with this procedure, they recommended CCRT with TPF as a standard treatment for locally advanced squamous cell carcinoma. The overall survival rate for patients with unresectable T4 tumors in our study was 56%, which agrees with the rate reported by Shiga et al Although the sample size for both studies was small, the prognosis for patients treated with CCRT tended to be better than for those treated with the other modalities. Especially noteworthy is that 80% of the patients with T3 or T4 disease without lymph node metastasis or expansive dural invasion in our study have survived without disease for >3 years.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the basis of favorable oncologic results for T4 diseases obtained with this procedure, they recommended CCRT with TPF as a standard treatment for locally advanced squamous cell carcinoma. The overall survival rate for patients with unresectable T4 tumors in our study was 56%, which agrees with the rate reported by Shiga et al Although the sample size for both studies was small, the prognosis for patients treated with CCRT tended to be better than for those treated with the other modalities. Especially noteworthy is that 80% of the patients with T3 or T4 disease without lymph node metastasis or expansive dural invasion in our study have survived without disease for >3 years.…”
Section: Discussionsupporting
confidence: 91%
“…To improve the locoregional control of CCRT, Tsukuda et al developed CCRT using TPF. In the phase I trial, CCRT with TPF was well tolerated and efficacious for patients with locally advanced squamous cell carcinoma of the head and neck, but was associated with a high incidence(79%) of severe mucositis (grade 3 and 4), which prevented this protocol from being accepted as standard therapy for advanced head and neck cancers. Irradiation of temporal bone cancer, however, involves only a limited part of the pharyngeal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Bacciu et al reported 26 temporal bone carcinomas (57.8%) on the right side and 19 (42.2%) on the left side . Shiga et al reported that 9 patients had EACSCC on the right side, and 5 had EACSCC on the left side . On the contrary, Gidley et al reported left dominance (55%) and concluded that SCC in the temporal bone was more commonly found on the left ear of middle‐aged to elderly men .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection can be difficult owing to complex regional anatomy and can often result in damage to the facial nerve and hearing loss 11. Metastatic adenocarcinoma of the temporal bone from a primary in the lung presenting with cranial nerve palsy has been described 12.…”
Section: Discussionmentioning
confidence: 99%